Assessing the Contribution of an HtrA Family Serine Protease During Borrelia turicatae Mammalian Infection - Jackson-Litteken, Clay D.; Zalud, Amanda K.; Ratliff, C. Tyler; Latham, Jacob I.; Bourret, Travis J.; Lopez, Job E.; Blevins, Jon S. (Frontiers in Cellular and Infection Microbiology, 2019)
Tick-borne relapsing fever (TBRF), characterized by recurring febrile episodes, is globally distributed and among the most common bacterial infections in some African countries. Despite the public health concern that this disease represents, little is known regarding the virulence determinants required by TBRF Borrelia during infection. Because the chromosomes of TBRF Borrelia show extensive colinearity with those of Lyme disease (LD) Borrelia, the exceptions represent unique genes encoding proteins that are potentially essential to the disparate enzootic cycles of these two groups of spirochetes. One such exception is a gene encoding an HtrA family protease, BtpA, that is present in TBRF Borrelia, but not in LD spirochetes. Previous work suggested that btpA orthologs may be important for resistance to stresses faced during mammalian infection. Herein, proteomic analyses of the TBRF spirochete, Borrelia turicatae, demonstrated that BtpA, as well as proteins encoded by adjacent genes in the B. turicatae genome, were produced in response to culture at mammalian body temperature, suggesting a role in mammalian infection. Further, transcriptional analyses revealed that btpA was expressed with the genes immediately upstream and downstream as part of an operon. To directly assess if btpA is involved in resistance to environmental stresses, btpA deletion mutants were generated. btpA mutants demonstrated no growth defect in response to heat shock, but were more sensitive to oxidative stress produced by t-butyl peroxide compared to wild-type B. turicatae. Finally, btpA mutants were fully infectious in a murine relapsing fever (RF) infection model. These results indicate that BtpA is either not required for mammalian infection, or that compensatory mechanisms exist in TBRF spirochetes to combat environmental stresses encountered during mammalian infection in the absence of BtpA.